Synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates using Na-Y zeolite catalyst - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synlett, 2006)
A simple, efficient, and environmentally benign methodology for the synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates in the presence of the highly active and reusable solid base catalyst Na-Y zeolite is demonstrated.
Keywords: Alkylation; alkylene carbonate; Amine; Amino alcohols; zeolite

Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Dimethyl [(2R,3R,5S)-5-phenylmorpholine-2,3-diyl]diacetate as a designer substrate in the syntheses of important heterocyclic scaffolds - Pandey, Ganesh; Gaikwad, Amrut L.; Gadre, Smita R. (Asian Journal of Organic Chemistry, 2012)
Designed scaffold dimethyl [(2R,3R,5S)-5-phenylmorpholine-2,3-diyl]diacetate was synthesized in optically pure form by photoinduced one-electron reductive beta-activation of an alpha,beta-unsaturated carbonyl moiety for stereoselective C-C bond formation. Use of the morpholine derivative as a ``chemical multitalent'' is demonstrated by its easy transformation to valuable heterocyclic building blocks such as methyl [(2R,3S)-3-hydroxy-5-oxopyrrolidin-2-yl]acetate, methyl [(2R,3S)-3-amino-5-oxotetrahydrofuran-2-yl]acetate, (3R,4S)-4-aminohexane-1,3,6-triol, and 2-[(2R,3S)-3-aminotetrahydrofuran-2-yl]ethanol.
Keywords: Amino alcohols; butyrolactams; butyrolactones; morpholines; photoinduced electron transfer reactions

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions